Assessing requirements for sustained ocean color research and operations - Schueler, C.; Yoder, J.; Antoine, David; del Castillo, C.; Evans, R.; Mengelt, C.; Mobley, C.; Sarmiento, J.; Sathyendranath, S.; Siegel, D.; Wilson, C. (2011)
Satellite measurements of ocean color provide a unique global perspective on the health of marine ecosystems and their contribution to the global cycle of nutrients, oxygen, and carbon, as well as their response to long-term climate change. The nation is at risk of losing access to ocean color data because existing satellite sensors are aging and planned new satellite missions might not be able to acquire data at the accuracy required for climate research. This paper summarizes the results of a National Research Council report on the minimum requirements to sustain global ocean color measurements for research and operational use and options to minimize the risk of an ocean color data gap.